Gender differences in the impact of sleep duration on common mental disorders in school students - Beatriz Tosé Agathão; Claudia Souza Lopes; Diana Barbosa Cunha; Rosely Sichieri (BMC, 2020)
Abstract Background Common mental disorders (CMD) in children and adolescents can be initial and non-specific manifestations of more serious mental diseases and often persist into adulthood. Therefore, early detection is important, as is the identification of the factors that impact development. Insufficient sleep represents one of the most common and potentially remediable risks to mental health in children and adolescents for whom chronic sleep loss has become normal. This study aims to investigate the influence of sleep duration on CMD in schoolchildren and adolescents. Methods The data for this longitudinal study were derived from the community trial Parents, Students, Community Health Agents and Teachers for Healthy Eating (PAAPAS) in 2016 (N = 2743), with fifth and sixth graders from 18 public schools of Duque de Caxias, Rio de Janeiro, Brazil. CMD were assessed by the General Health Questionnaire (GHQ-12) at baseline and at a 9-month follow-up. Sleep duration was evaluated at baseline and was categorized as short, adequate or long according to age group. The effect of sleep duration on common mental disorders was analysed by sex using linear mixed-effects models. Results At baseline, the frequency of CMD was 33.2% and was higher in boys than in girls and higher among students with short sleep duration. There was an increase in the CMD score over time among girls with short sleep duration (p < 0.01). Among boys, a similar trajectory of the CMD score was observed in the subgroups with short and long sleep duration, but there was a significant reduction in the subgroup with long sleep duration (p = 0.05). Conclusion Changes in common mental disorder patterns differ according to sex, and short sleep duration seems to be problematic for students' mental health. The promotion of health strategies that involve the family and school environment, such as later school hours, could help change this scenario.